Chronic effects of six micro/nano-Cu2O crystals with different structures and shapes on Daphnia magna. (August 2015) - Wang, Huihui; Fan, Wenhong; Xue, Feng; Wang, Xiaolong; Li, Xiaomin; Guo, Lin
Abstract: Six micro/nano-Cu2 O crystals evolved from cubes to corner-truncated cubes, vertex-truncated octahedrons and ultimately to octahedrons were synthesized in this work, and the chronic toxicity of these crystal suspensions (10 μg L −1 ) for Daphnia magna was investigated over a 30-day period. Our results indicated that the octahedrons had the most evident toxic effect, but the cubes were minimally toxic. The mortality rate of the octahedral treatment was as high as 86.7%, whereas that of the cubic treatment was only 6.7%. Significant inhibitions in growth and reproduction were observed under octahedral exposure, with reduced impacts from vertex-truncated octahedrons, corner-truncated cubes, and cubic crystals. The chronic effects of different micro/nano-Cu2 O crystals were related to their solubility in the gut of the organisms. The solubility of micro/nano-Cu2 O crystals was influenced by surface atomic arrangement and diverse surface activity. Thus, the structure and intestinal solubility of nanocrystals should be evaluated for long-term toxicity. Highlights: First time to compare the chronic toxicity of six micro/nano-Cu2 O crystals. Toxicity differences are related to solubility of materials in gut of organisms. Surface activity of the material can result in the differences of toxicity. Surface atom arrangement plays a role in the differences of toxicity essentially. Abstract : The chronic effects of six micro/nano-Cu2 O crystals were dependent on their surface activity and atomic arrangement.